2008
DOI: 10.1039/b810195g
|View full text |Cite
|
Sign up to set email alerts
|

DNA-embedded Au/Ag core–shell nanoparticles

Abstract: Here, we synthesized highly stable DNA-embedded Au/Ag core-shell nanoparticles (NPs) by a straightforward silver-staining of DNA-modified Au nanoparticles (AuNPs); unlike conventional DNA-surface modified NPs that present particle stability issues, DNA-embedded core-shell NPs offer an extraordinary stability with nanoscale controllability of silver shell thickness; these DNA-embedded core-shell NPs show excellent biorecognition properties and Ag shell-thickness-based optical properties, distinctively different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 26 publications
6
80
0
3
Order By: Relevance
“…Hydroquinone has a weak redox potential (E° = −0.7 V vs. NHE) [41], and is therefore unable to reduce the Ag [42,43]. Furthermore, Lim et al have recently reported the successful formation of an Ag shell layer on Au core NPs using hydroquinone as the reducing agent [44]. On the basis of these results and previous reports, it is proposed that Au core -Ag shell bimetallic NPs, as shown in Figure 1(d), were successfully synthesized on the surfaces of ZnO whiskers via a multi-step process.…”
Section: Auagnps Synthesis On the Zno Whiskersmentioning
confidence: 99%
“…Hydroquinone has a weak redox potential (E° = −0.7 V vs. NHE) [41], and is therefore unable to reduce the Ag [42,43]. Furthermore, Lim et al have recently reported the successful formation of an Ag shell layer on Au core NPs using hydroquinone as the reducing agent [44]. On the basis of these results and previous reports, it is proposed that Au core -Ag shell bimetallic NPs, as shown in Figure 1(d), were successfully synthesized on the surfaces of ZnO whiskers via a multi-step process.…”
Section: Auagnps Synthesis On the Zno Whiskersmentioning
confidence: 99%
“…[17,18] Additionally, hydroquinone has also been used to grow thin silver shells on gold nanoparticles as a means to amplify their scattering properties, but this was restricted to very thin shells on small spherical particles. [19,20] However, we demonstrate here that these processes can be utilized in a much more controlled manner, thus allowing exquisite morphology control. Based on our previous experience on the reshaping of single-crystal gold nanorods into octahedrons, [21] we decided to explore the coating of the same type of nanorods with silver, so as to tune the morphology of the resulting core-shell particles.…”
mentioning
confidence: 95%
“…The more ligand added, the rougher surface the Au nanoshell presents (Figure 2e and 2f). The phenomenon can be explained by the theory reported in our previous paper: the strong binding property of 4 MBA in this system forces selective deposition of Au at the ligand-deficient interface between Au NSs and PSPAA domain to form dense Au nanoworms, resulting in the rough surface [28][29][30].…”
Section: Scheme 1 Schematics Showing a General Methods For Growingmentioning
confidence: 99%